Análise do campo térmico na área urbana de Ponte Nova, Minas Gerais - Allocca, Rodson de Andrade (2018)
The present research, inserted in the recent context of the increase of the researches in urban climate in the small and medium cities, made a study on the thermal field, in seasonal episodes, observed in the urban area of the municipality of Ponte Nova, located in the region of the Zone of the Forest of Minas Gerais. With the objective of analyzing the behavior of the thermal field, within the theoretical perspective of the Urban Climate System, we tried to identify how the geoecological factors (relief, slope orientation, altimetry, etc.) are related to the georbanos factors (Sky View Factor, density of population, patterns of land use and occupation, etc.) in the configuration of thermal standards. In order to reach the proposed objective, an air temperature monitoring network was structured and used, based on the installation of fixed points of data collection and also on the technique of mobile transects. In addition, a cartographic database was produced and organized about the municipality. For the development of the thermal field analyzes, the air temperature data collected were submitted to an experimental correction method developed specifically to meet the reality of the research. After the thermal data correction, spatialization of the data was generated through the Inverse Distance Weighting (IDW) interpolation technique in ArcMap software. Results were analyzed for the understanding of the behavior of the thermal field and the verification of the relationship of influence of the site and / or the urban environment on the spatialization pattern of the temperature values recorded. The results demonstrated the occurrence of considerable intraurban thermal differences, being the biggest thermal difference observed in the winter episode, when the Atlantic Polar Mass acted on the region where the municipality of Ponte Nova is located. The variety of climatic factors observed in the scope of the research made the analysis a complex task. However, there is a strong indication of the influence of human actions on the observed thermal values.